“Janela Amazônia”: Introductory considerations on Television and Cinema in The Amazon (Research, Society and Development, 2026)
The goal of this article is to present introductory considerations on television, cinema, and audiovisual production in the Amazon, based on the experience and reflections developed within the “Janela Amazônia” research group, based in Belém do Pará. The text argues for audiovisual practice as a language, an artistic practice, and a research method capable of producing situated knowledge by articulating creation, critical reflection, and territorial experience. In a context marked by the intensification of information flows and the advancement of artificial intelligences, the urgency of critical education and the dissemination of knowledge is emphasized, especially in the field of the arts. The discussion draws on Boaventura de Sousa Santos’ concepts of transcoding and the double epistemological break to argue that academic knowledge must return to common sense, transforming society while also being transformed by it. Considering the specificities of Brazil’s Northern region, the article highlights the strategic role of audiovisual media in cultural mediation, memory-building, and the democratization of access to knowledge in the Amazonian region, marked by historical inequalities, geographic isolation, and symbolic invisibility. In addition, it addresses the centrality of the image in the constitution of memory and identities, emphasizing its symbolic, epistemic and aesthetic functions. Finally, it reaffirms that thinking about Amazonian audiovisual practices entails recognizing the territory’s plurality, the dispute over imaginaries, and the power of collective practices of creation, writing, and exchange among artists as essential forms of research and cultural production.